2015
DOI: 10.1016/j.ajpath.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sox10, HIF-1α, Survivin, and YAP by Minocycline in the Treatment of Neurodevelopmental Handicaps following Hypoxic Insult

Abstract: Premature infants are at an increased risk of developing cognitive and motor handicaps due to chronic hypoxia. Although the current therapies have reduced the incidence of these handicaps, untoward side effects abound. Using a murine model of sublethal hypoxia, we demonstrated reduction in several transcription factors that modulate expression of genes known to be involved in several neural functions. We demonstrate the induction of these genes by minocycline, a tetracycline antibiotic with noncanonical functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Interestingly, the expression levels of Yap and Sox10, two transcription factors that modulate expression of multiple genes with neural functions similar to findings in mice 29 , were also significantly decreased in the organoids under hypoxic stress and rescued by minocycline (Supplementary Fig. 11B, C).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Interestingly, the expression levels of Yap and Sox10, two transcription factors that modulate expression of multiple genes with neural functions similar to findings in mice 29 , were also significantly decreased in the organoids under hypoxic stress and rescued by minocycline (Supplementary Fig. 11B, C).…”
Section: Resultssupporting
confidence: 72%
“…In prior work in the mouse, we have found that minocycline prevents the downregulation by hypoxia of a transcriptional program of neurogenesis controlled by YAP and Sox10 29 . In particular, these transcription factors regulate genes involved in proliferation, apoptosis, and neural development 26 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Hypoxia modulates SIAH2 ubiquitin E3 ligase, which enhances the formation of a complex between YAP1 and HIF-1α, which increases HIF-1α stability [ 33 ]. Hypoxia also increases YAP1 gene expression [ 34 ]. The evidence provided here demonstrates that upregulation of YAP1 expression by PD-L1 may confer TKI resistance by increasing ROS generation and therefore promoting HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%